Germinação e crescimento de plântulas de Libidibia ferrea Mart. ex. Tul. em função do peso de semente e condições de temperatura e luz - Gomes, Fernanda Melo (2014)
The aim of this work was to study the seed germination and seedling establishment of Libidibia ferrea depending on the seed weight, temperature and light. Seeds of L. ferrea were classified into three weight classes (light, medium and heavy) and were carried out temperature and light bioassay in laboratory, beyond the shading experiment in greenhouse. For the laboratory experiment, the shoot growth of seedlings showed better performance in the absence of light and it is best developed at 25 and 30°C, while the root has just developed better under 30°C. Medium and heavy seeds showed more vigorous seedlings under 50% and 70% shade. It was concluded that the heavy seeds (> 0.12 g) have better germination performance and produced more vigorous seedlings.